Women with Disabilities in Nepal (Saptagandaki Journal, 2018)
The women who have one or more impairments and experience barriers in society are the women with disability (WWD). Disabled women of all ages, in rural and urban areas, regardless of the severity of the impairment, sexual preference and cultural background or whether they live in the community or an institution are recognized as the WWD. As the Person with Disabilities are deprived, isolated, marginalized and excluded groups of the society, the women who have disability are one of the components of them. The social status of disabled women varies according to individual circumstances and to the country in which they live. Being a member of United Nations, Nepal recognized the human rights of people with disability in the year 1981. Accordingly, it enacted a special law known as the Disabled Persons Protection and Welfare Act, 1982 but even after 36 years of existence, the people with disabilities are often excluded from the mainstream of society and denied their human rights. Nepal is rich with legislative provisions but there is discrepancy between legislation and practices. Social security system is very poor in Nepal; disabled as well as economically marginalized people have not received any kind of social protection (food, shelter, clothes, health, education, and training). The strongest rights to social security may turn out to be nothing more than unfulfilled promises. Again most of the services are situated in urban areas and disabled people from rural areas at more risk. So it is mandatory to cater necessary services to all women with disabilities living in any part of Nepal for the respect, protect and fulfilling the commitment of government by human rights Instruments. The Sapta Gandaki JournalVol. IX, 2018 Feb. Page: 17-25